Scientific inquiry in the learning of natural sciences for social skills in students and process management for health - Víctor Mario Culqui Rojas; Nathalie Parra Gálvez; Gladys Espinoza Vásquez; Violeta Leonor Romero-Carrión; Luz Antonia Barreto Espinoza; Luz Karen Flores Pérez (Revista Finlay, 2024)
Foundation: the development of social skills acquired through scientific inquiry in health management processes by students who work as physical education teachers, as well as their online evaluation are fundamental aspects, both in the comprehensive training of staff, the improvement of process management, and the corporate image of the institution. Objective: evaluate the state of physical activities for the training of teachers of the educational entity. Methods: the research was non-experimental with a transectional design. A diagnosis was made based on observation and data collection through the survey. The sample was the group of students who work as teachers. Two variables were evaluated in one of the four dimensions of corporate image. Results: the educational institution lacks a solid corporate image, without promoting digital competencies and social skills of teachers. 76 % of those surveyed rated the social skills for learning in the services offered to the user dimension with a medium level, 14 % low and 10 % high. 55 % rated process management for user health at a medium level, 8 % low and 10 % high. The majority did not perceive that the institution offered a variety of services. Conclusions: it’s necessary to develop acquired social skills as a powerful tool to help students manage their needs and health care.